2009
DOI: 10.1063/1.3254444
|View full text |Cite
|
Sign up to set email alerts
|

Pr 3 + -doped fluoro-oxide lithium glass as scintillator for nuclear fusion diagnostics

Abstract: Experimental results are presented on the neutron scintillating properties of a custom-designed Pr3+ (praseodymium)-doped lithium (Li) glass. Luminescence was observed at 278 nm wavelength, originating from the 5d-4f transition. Time-resolved measurements yielded about 20 ns decay times for ultraviolet and x-ray excitation while much faster decay times of about 6 ns were observed for alpha particle and neutron excitation. Actual time-of-flight data in laser fusion experiments at the GEKKO XII facility of the I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 15 publications
2
45
0
Order By: Relevance
“…The efficacy of a hydrothermal-method-grown ZnO crystal as a scintillator for UV region has been previously demonstrated (Furukawa et al, 2008;M. Tanaka et al, 2007;Nakazato et al, 2009), wherein the reported decay time of the ZnO scintillator was 1ns for EUV excitation at 13nm using Ag-plasma EUV laser. However, a faster response time is needed.…”
Section: Zinc Oxide (Zno)mentioning
confidence: 99%
See 2 more Smart Citations
“…The efficacy of a hydrothermal-method-grown ZnO crystal as a scintillator for UV region has been previously demonstrated (Furukawa et al, 2008;M. Tanaka et al, 2007;Nakazato et al, 2009), wherein the reported decay time of the ZnO scintillator was 1ns for EUV excitation at 13nm using Ag-plasma EUV laser. However, a faster response time is needed.…”
Section: Zinc Oxide (Zno)mentioning
confidence: 99%
“…The highest doping of Pr +3 was found to be 3% at the present manufacturing procedure. The preliminary characteristics were reported in (Murata et al, 2009). …”
Section: Pr-doped Glassmentioning
confidence: 99%
See 1 more Smart Citation
“…(1)(2)(3) For inertial confinement fusion (ICF), 20Al(PO 3 ) 3 -80LiF (APLF) glass samples doped with Ce, praseodymium (Pr), neodymium (Nd), and erbium (Er) have also been investigated for neutron detector applications. (4,5) These APLF samples are sensitive to neutrons because of their high concentration of lithium ( 6 Li). APLF glass has a fast response without afterglow compared to conventional Li glass neutron scintillators such as GS2 (Saint-Gobain).…”
Section: Introductionmentioning
confidence: 99%
“…For these purposes, a fast-response 6 Li glass scintillator (APLF80) has been developed [4]. The energy peak of the down-scattered neutrons from DD fusion is at 0.27 MeV, matching the resonant peak in the cross section of neutron detection for a 6 Li scintillator [1].…”
Section: Introductionmentioning
confidence: 99%